KNOWLEDGE AND ATTITUDE OF MEN TOWARDS RISK FACTORS INFLUENCING MATERNAL MORTALITY IN MAGUME COMMUNITY, ZARIA - Ibrahim Mohammed Jimoh; Usman Nafisa; Sani Zakari Muhammad; Omole Victoria Nanben (Ntec Specialist, 2019)
Background: Most studies related to maternal mortality have focused mainly on direct clinical causes. However, it is imperative to look at the importance of tackling background predisposing factors in a bid to reducing deaths occurring in this vulnerable group. Innovative and effective options towards preventing as well as reducing maternal deaths must include active participation of men, who more often than not are not knowledgeable about these risk factors. Aims: To assess the knowledge and attitude of men towards risk factors influencing maternal mortality in Magume Community, in Zaria LGA. Methods: A descriptive cross-sectional study was carried out in 2016 using a pretested semi-structured interviewer-administered questionnaire. A total of 170 respondents were sampled using a multistage sampling technique. Data were analysed based on descriptive statistics, chi-square and Fisher's exact test using SPSS version 21. The level of statistical significance was set at p less than 0.05. The results were presented using tables and charts. Results: The mean age of the respondents was 38(±11.2) years. Knowledge scores show that approximately 46% of the respondents had good knowledge, while 40% had poor knowledge and 14% had fair knowledge. Lack of ANC services during pregnancy was the most commonly identified (93.1%) maternal mortality risk factor and lack of family planning was the least identified (34.3%). Attitude to maternal mortality risk factors was negative in half (50.9%) of the respondents. There was a statistically significant relationship between educational level and occupation with both knowledge and attitude scores. Conclusion: This cross-sectional study has highlighted the need for increased male involvement and participation in maternal health issues. Interventions such as health education and community mobilization that aims to educate men on risk factors and danger signs associated with poor maternal health outcomes should be carried out in this area.